Algebra: A Combined Approach (4th Edition)

Published by Pearson
ISBN 10: 0321726391
ISBN 13: 978-0-32172-639-1

Chapter 11 - Section 11.2 - Solving Quadratic Equations by Completing the Square - Exercise Set - Page 775: 5



Work Step by Step

$x^{2}-6x+9=0$ Use the quadratic formula to solve this equation. The formula is $x=\dfrac{-b\pm\sqrt{b^{2}-4ac}}{2a}$. For this equation, $a=1$, $b=-6$ and $c=9$ Substitute: $x=\dfrac{-(-6)\pm\sqrt{(-6)^{2}-4(1)(9)}}{2(1)}=\dfrac{6\pm\sqrt{36-36}}{2}=...$ $...=\dfrac{6\pm\sqrt{0}}{2}=\dfrac{6}{2}=3$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.